(untitled) (Medico Legal Update, 2019)
Interest and care for the people around the farming village to maintain the continuity of rural life. Efforts are also needed to create younger farming villages by providing various facilities of convenience to help ensure the young people’s settlement for rural life and also by organizing communities for those pursuing rural life. In addition, since pursuing rural life, it will be necessary to secure the profitability of crops by continuously participating in various agricultural education and visiting farming villages in advanced countries for securing economic power. The government and local governments will need to provide all facilities which help all people to easily settle for rural life by creating an environment similar to the cities through the environmental improvement projects of farming villages. Those pursuing rural life will need to explore various ways of communicating with their family and offer them opportunities to experience farming.